IMAM HATIP SCHOOL (IMAM HATIP LISESI): Islamic School in Contemporary Secular Turkey - Junaedi, Mahfud (Analisa: Journal of Social Science and Religion, 2016)
Imam Hatip schools have been a crucial and controversial Islamic education in a contemporary secular Turkey. The majority of Imam Hatip School students come from families who live and conduct their relations in accordance with Islamic norms and principles. Many conservative, religious-minded parents in rural and small town (in central and eastern Turkey) send their children after primary school to an Imam Hatip High school because this is the only school type in which the children can study Islamic subjects besides the general curriculum and the teachers are believed to impart traditional moral values. Many of those parents would, however, wish their children to pursue modern careers and fid more prestigious and better-paid jobs than that of a modest preacher. Today Imam Hatip schools do not only produce Imams (leaders of prayer) and hatips (deliver khutba at every Friday sermon), but also design to cultivate religious sensibilities (dini hassasiyetler) in their students. The schools aim to heighten their student’s awareness of faith and promote the notion that religion should play a substantial role in the life of individuals and society. The most important is that Imam Hatip schools play an important role in Turkey’s pious community and make the country more Islamic.